Integrating Technology in Hospital Supply Chain: Pathway to a Sustainable Healthcare Ecosystem - Islam, Shaiful; Habib, Md. Mamun (International Journal of Supply Chain Management, 2024)
The importance of sustainable practices within hospital supply chains has never been more pronounced than in the contemporary healthcare landscape, particularly in the wake of global health challenges. This research paper extends the discourse on sustainable hospital supply chain management (SHSCM) by examining the role of Technology Supply Chain Applications (TSCAs) as a catalyst for Sustainable Societal Advancement (SSA). Drawing from a substantial sample size of 401 respondents and employing factor analysis via structural equation modeling (SEM), the study upholds methodological integrity and rigor. The paper unveils a novel perspective on how TSCAs can revolutionize SHSCM by promoting efficiency, transparency, and collaboration, which are crucial for societal progression in the post-pandemic era. The findings affirm both hypotheses, with the data revealing a significant positive relationship between TSCAs and SHSCM, and between CIF-infused SHSCM and SSA. The implications of these relationships are manifold, indicating that the integration of technology within hospital supply chains is not merely a facilitator of internal process improvements but also a strategic contributor to societal well-being. The paper also navigates through the complexities of implementing TSCAs in SHSCM, presenting a balanced viewpoint by considering the limitations, such as the study's geographical and demographic specificity, which may affect the generalizability of the results. Beyond confirming the positive impact of TSCAs on SHSCM and SSA, the research offers actionable insights for healthcare practitioners and policymakers. It emphasizes the need for strategic investments in technology to enhance the resilience and sustainability of hospital supply chains. The study concludes by advocating for a concerted effort towards embedding technology at the core of hospital supply chains. This strategic pivot is crucial not only for the recovery of healthcare systems but also for laying the foundation for a more sustainable and socially responsible future. It highlights the need for a comprehensive and collaborative approach that leverages technology to overcome current challenges and drive forward the agenda of sustainable development within healthcare and beyond. Through this research, a compelling case is made for the strategic enhancement of technology within hospital supply chains as a means to foster societal advancement, providing a blueprint for future research endeavors aimed at bolstering the global healthcare landscape.